2017
DOI: 10.1016/j.immuni.2017.01.009
|View full text |Cite
|
Sign up to set email alerts
|

CD49a Expression Defines Tissue-Resident CD8 + T Cells Poised for Cytotoxic Function in Human Skin

Abstract: SummaryTissue-resident memory T (Trm) cells form a heterogeneous population that provides localized protection against pathogens. Here, we identify CD49a as a marker that differentiates CD8+ Trm cells on a compartmental and functional basis. In human skin epithelia, CD8+CD49a+ Trm cells produced interferon-γ, whereas CD8+CD49a− Trm cells produced interleukin-17 (IL-17). In addition, CD8+CD49a+ Trm cells from healthy skin rapidly induced the expression of the effector molecules perforin and granzyme B when stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
474
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 484 publications
(498 citation statements)
references
References 50 publications
24
474
0
Order By: Relevance
“…Transcriptional profiling has been reported for mouse CD8 + TRM in which CD8 + memory T cells isolated from a barrier site (skin, intestine or lung) were compared with spleen (Mackay et al, 2016; Mackay et al, 2013). In human studies, CD8 + TRM isolated based on CD103 expression from individual tissues (lung, skin) have been profiled in comparison to blood subsets (Cheuk et al, 2017; Hombrink et al, 2016). Here, we employed an innovative and comprehensive approach to assess differences in putative circulating and resident populations within tissues by directly comparing CD69 + memory subsets from a lymphoid and mucosal site (spleen and lung) with the corresponding CD69 − subset from each tissue as well as CD69 − TEM from blood for both CD4 + and CD8 + lineages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptional profiling has been reported for mouse CD8 + TRM in which CD8 + memory T cells isolated from a barrier site (skin, intestine or lung) were compared with spleen (Mackay et al, 2016; Mackay et al, 2013). In human studies, CD8 + TRM isolated based on CD103 expression from individual tissues (lung, skin) have been profiled in comparison to blood subsets (Cheuk et al, 2017; Hombrink et al, 2016). Here, we employed an innovative and comprehensive approach to assess differences in putative circulating and resident populations within tissues by directly comparing CD69 + memory subsets from a lymphoid and mucosal site (spleen and lung) with the corresponding CD69 − subset from each tissue as well as CD69 − TEM from blood for both CD4 + and CD8 + lineages.…”
Section: Discussionmentioning
confidence: 99%
“…We found phenotypic heterogeneity based on the core markers, particularly among CD4 + TRM, and additional tissue heterogeneity has been reported in CyTOF profiling of human tissue T cells (Wong et al, 2016). CD103 expression by mouse intestinal TRM (Bergsbaken and Bevan, 2015) and CD49a in human skin memory T cells (Cheuk et al, 2017), have been shown to delineate distinct functional capacities, and dissecting human TRM heterogeneity will be an important area of focus in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional profiling has been reported for mouse CD8 + TRM in which CD8 + memory T cells isolated from a barrier site (skin, intestine or lung) were compared with spleen Mackay et al, 2013). In human studies, CD8 + TRM isolated based on CD103 expression from individual tissues (lung, skin) have been profiled in comparison to blood subsets (Cheuk et al, 2017;Hombrink et al, 2016). Here, we employed an innovative and comprehensive approach to assess differences in putative circulating and resident populations within tissues by directly comparing CD69 + memory subsets from a lymphoid and mucosal site (spleen and lung) with the corresponding CD69 − subset from each tissue as well as CD69 − TEM from blood for both CD4 + and CD8 + lineages.…”
Section: Discussionmentioning
confidence: 99%
“…59 In human skin, the presence or absence of CD49a expression can divide T RM s into IFN-γ or IL-17-Producing cells and associated with type 1 or type 17 effector T cell-related disease settings. 62 However, the molecular and cellular control of the type 17 effector program in CD8 + T cells or T RM cells remains unclear.…”
Section: Tissue Specific Features Of Trm Cellsmentioning
confidence: 99%